(untitled) (Scientific journal of the Fergana State University, 2025)
The paper investigates the hydraulic activity of quartzite waste from induction furnaces when used in cement–sand mortars. Experimental mixtures were prepared by partially replacing Portland cement with quartzite waste in amounts of 10–30 wt.%. The flexural and compressive strength of the specimens was determined at the ages of 7 and 28 days. It was established that the incorporation of 15–20% quartzite waste leads to an increase in strength compared with the control mixture, which is associated with its participation in hydration processes and the densification of the cement stone structure. An increase in the additive content above 20% results in a decrease in strength due to a reduction in the clinker phase content.